Numerical investigation of ohmically dissipated mixed convective flow - Hussain, Majid; Ali, Akhtar; Yao, Shao-Wen; Ghaffar, Abdul; İnç, Mustafa (Elsevier, 2022)
The impact of ohmic heating and thermal radiation plays a prominent role in industrial and technological applications, for example aerodynamic heating and process flows. Thus the current study provides the convective heat transfer of magnetohydrodynamics mixed convection flow towards a penetrable stretching wedge with ohmic heating and thermal radiation. By utilizing suitable similarity transformation the set of ODEs are transformed to set of highly nonlinear PDEs. The reduced equations are elucidated by employing bvp4c method in MATLAB software. The effects of numerous emerging parameters were examined and disclosed graphically. In contrast, the inclusion of stretching wedge, the temperature and velocity distribution upraises with the increase of R. Numerical outcomes of skin friction and Nusselt number are disclosed by addition of these parameters. At R = 0.6, the upgraded values of radiation parameter upsurges the temperature gradient. The similar trend is noted at R = 1.2. The augmented values of Ec rises the temperature gradient for both the cases of wedge (R less than or greater than 1). Observations shows that varying R and M upsurges the absolute values of surface drag force. However increased values of M lessened the temperature gradient.
Keywords: Numerical technique; Convective transport; Ohmic heating; Stretching porous wedge; Suction/injection; Laminar flow